Pemberdayaan Kampung Iklim dan Dampaknya Terhadap Kesejahteran Masyarakat di Kelurahan Mangunsari Sidomukti Salatiga - Saipullah Hasan (UIN Siber Syekh Nurjati Cirebon, 2023)
Climate villages are efforts and methods carried out by the community as a response to the problem of climate change. The aim of this research is to determine the implementation of climate village empowerment by the community and its impact on community welfare. The research location is Mangunsari Village, Sidomukti District, Salatiga City. The research method uses qualitative with a descriptive approach. Data collection was carried out through observation and interviews with parties directly involved in the formation of climate villages. The research results show that the implementation of climate village empowerment is carried out by implementing various programs, namely creating biopore areas, managing waste through infiltration wells, managing waste and reforestation on limited land. These various programs have had an impact in the form of social protection from the negative impacts of climate change through the formation of social institutions, making the environment greener and healthier and increasing community food security.Climate villages are efforts and methods carried out by the community as a response to the problem of climate change. The aim of this research is to determine the implementation of climate village empowerment by the community and its impact on community welfare. The research location is Mangunsari Village, Sidomukti District, Salatiga City. The research method uses qualitative with a descriptive approach. Data collection was carried out through observation and interviews with parties directly involved in the formation of climate villages. The research results show that the implementation of climate village empowerment is carried out by implementing various programs, namely creating biopore areas, managing waste through infiltration wells, managing waste and reforestation on limited land. These various programs have had an impact in the form of social protection from the negative impacts of climate change through the formation of social institutions, making the environment greener and healthier and increasing community food security.